2008
DOI: 10.1038/nri2397
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring T-cell receptor signals by proximal negative feedback mechanisms

Abstract: The T-cell receptor (TCR) signalling machinery is central in determining the response of a T cell (establishing immunity or tolerance) following exposure to antigen. This process is made difficult by the narrow margin of self and non-self discrimination, and by the complexity of the genetic programmes that are induced for each outcome. Recent studies have identified novel negative feedback mechanisms that are rapidly induced by TCR engagement and that have key roles in the regulation of signal triggering and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
282
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(290 citation statements)
references
References 110 publications
5
282
0
3
Order By: Relevance
“…Central mediators of T-cell adhesion are integrins as, for example, the aLb2 integrin leukocyte function-associated antigen-1 (LFA-1), whose activation is mediated by chemokines or antigen receptor encounter and the b1 family of integrins (very late antigen; a4b1, a5b1 and a6b1). LFA-1 activation after TCR stimulation, also referred to as inside-out signaling, relies on a signaling module composed of the transmembranous adapter LAT (linker for activation of T cells) and the cytosolic adaptors SLP-76 (76-kDa src homology 2 domain-containing leukocyte phosphoprotein) and Gads (Grb2-related adaptor downstream of Shc) [1,2]. Two additional adapter molecules, adhesion and degranulation promoting adaptor protein (ADAP) and 55-kDa src kinase associated phosphoprotein (SKAP-55), are recruited upon TCR-mediated phosphorylation of ADAP on Y 595 DDV or Y 651 DDV to the SH2-domain of SLP-76 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Central mediators of T-cell adhesion are integrins as, for example, the aLb2 integrin leukocyte function-associated antigen-1 (LFA-1), whose activation is mediated by chemokines or antigen receptor encounter and the b1 family of integrins (very late antigen; a4b1, a5b1 and a6b1). LFA-1 activation after TCR stimulation, also referred to as inside-out signaling, relies on a signaling module composed of the transmembranous adapter LAT (linker for activation of T cells) and the cytosolic adaptors SLP-76 (76-kDa src homology 2 domain-containing leukocyte phosphoprotein) and Gads (Grb2-related adaptor downstream of Shc) [1,2]. Two additional adapter molecules, adhesion and degranulation promoting adaptor protein (ADAP) and 55-kDa src kinase associated phosphoprotein (SKAP-55), are recruited upon TCR-mediated phosphorylation of ADAP on Y 595 DDV or Y 651 DDV to the SH2-domain of SLP-76 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to many other cell signaling pathways, the regulation of T cell activation is mediated largely through the regulation of protein posttranslational modifications. For instance, upon TCR ligation, lymphocyte-specific protein tyrosine kinase (LCK) phosphorylates the cytoplasmic tails of CD3, leading to the recruitment of ZAP-70, which potentiates the signaling cascade through phosphorylation of additional downstream substrates (1,2). Eventually, these early signaling events translate into the expression of new genes that are necessary for T cell effector function.…”
mentioning
confidence: 99%
“…Consequently, the kinase ZAP70 is recruited and activated (12), thereby phosphorylating the downstream adaptor molecules LAT and SLP76. This initiates multiple downstream pathways essential for T cell activation (13). It was suggested that Erk is activated by recruitment of the Grb2-SOS complex to the phosphorylated TCR via the adaptor protein Shc (14).…”
mentioning
confidence: 99%